Soft Skills of Czech Graduates - Jiří Balcar; Milan Šimek; Lenka Filipová (Review of Economic Perspectives, 2018)
Finding a job is easier for people who are better equipped with soft skills, as they are more productive. Therefore, this article deals with the evaluation of soft skills of graduates from Czech public universities. The results show that the same soft skills are required from university graduates as from the population as a whole (only problem solving is more pronounced with them), but the required level of these skills is 42% higher in the case of graduates. Unfortunately, employers perceive the level of graduates' soft skills insufficient as their level is by 16.46 to 31.15% lower than required. A more detailed analysis showed that, in terms of the development of soft skills, Czech universities provide a very homogenous service. Graduates of universities have nearly the same level of soft skills, while they can also identify similar strengths and weaknesses. These findings suggest that Czech universities should pay more attention to the systematic development of soft skills.
Keywords: I25; J23; J24; 330; graduates; language skills; professional skills; skill gap; soft skills; university